The Chosen Village Head Leadership in Carrying Out Government Duties: Analysis Study of Sidoharjo Village Head, Susukan, Semarang - Musta’an (International Journal of Seocology, 2019)
This study is entitled Leadership of Selected Village Heads in Carrying Out Government Duties (Analysis Study of Sidoharjo Village Head, Susukan District). The focus of this research is about how the Village Chief Leadership Style in Sidoharjo Village Head, Susukan District and the purpose of this study is to find out the Village Head Leadership Style in Sidoharjo Village Head, Susukan District. This study is classified as a descriptive study with core questionnaire instruments and data analysis techniques using the presentation of the frequency table of the results of questionnaires from respondents who have been determined based on questions about the 4 leadership styles based on expert theory used as grand theory in this study. The results showed that the leadership style that tends to be applied by village heads in carrying out their daily tasks and functions is the leadership style of Democracy. Democratic leadership style can be seen from the involvement or active participation of Sidoharjo village head in deciding problems in every activity of the organization / office. In addition, the Village Head also prioritizes democracy in his administration by always holding deliberations to reach consensus in making every decision.